2015
DOI: 10.1371/journal.pone.0124245
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum MicroRNA Levels Associate with Absence of High-Grade Prostate Cancer in a Retrospective Cohort

Abstract: To reduce treatment of indolent prostate cancer (PCa), biomarkers are needed to improve identification of patients with a low-risk of having aggressive disease. Over-treatment of these patients occurs because of uncertainty in the aggressiveness of the entire tumor based on the biopsies, which do not accurately sample multifocal tumors. Circulating microRNAs (miRNAs) are stable serum markers and differential miRNA levels occur in men with PCa. The goal of this study was to identify circulating miRNAs that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 38 publications
6
61
0
Order By: Relevance
“…e The samples from early relapse patients showed significantly decreased miR-494 expression levels (P = 0.016). f The samples from early relapsed patients showed significantly decreased let-7b expression levels (P = 0.002) Yang et al J Transl Med (2016) 14:108 that miR-141 has oncogenic characteristics in CRC and prostate cancer [42,43]. Yin et al identified miR-141 as a potential circulating biomarker for metastasis [44], consistent with our findings of high miR-141 expression in early relapsed CRC patients.…”
Section: Discussionsupporting
confidence: 87%
“…e The samples from early relapse patients showed significantly decreased miR-494 expression levels (P = 0.016). f The samples from early relapsed patients showed significantly decreased let-7b expression levels (P = 0.002) Yang et al J Transl Med (2016) 14:108 that miR-141 has oncogenic characteristics in CRC and prostate cancer [42,43]. Yin et al identified miR-141 as a potential circulating biomarker for metastasis [44], consistent with our findings of high miR-141 expression in early relapsed CRC patients.…”
Section: Discussionsupporting
confidence: 87%
“…However, the panels proposed for these groups do not overlap in miRNAs composition. On the other hand, downregulated results reported by Mihelich et al [95] concerning miR-93, miR-106a, miR-107, miR-130b and miR-451 were discordant with those reported in the studies made by Moltzahn et al [91], Li et al [97] and Bryant et al [98], which indicated that these miRNAs were upregulated in PCa patients.…”
Section: Circulating Mirnas In Prostate Cancermentioning
confidence: 54%
“…At the moment, the widest study about the clinical usefulness of circulating miRNAs has been performed by Mihelich et al [95], measuring the levels of 21 miRNAs in 50 BPH patients and 100 PCa patients in stages T1-T2, classified according to the Gleason score. The authors proposed a miRNA signature (let7a, miR-103, miR-451, miR-24, miR-26b, miR-30c, miR-93, miR-106a, miR-223, miR-874, miR-146a, miR-125b, miR-100, miR-107 and miR-130b) to predict with high accuracy the absence of high-grade PCa among the BPH and low-grade PCa patients.…”
Section: Circulating Mirnas In Prostate Cancermentioning
confidence: 99%
“…88 (Table 3) report more promising diagnostic and prognostic data than earlier studies. One reason for this improvement could be that combinations of different miRNAs 111,121 , miRNAs in combination with other markers 113,120 and miRNAs in blood cells 123 or exosomes 124 were investigated, rather than single miRNAs. However, the promising results of these studies are yet to be validated.…”
Section: [H1] Biofluid Mirnas In Prostate Cancermentioning
confidence: 99%